Innovation in the planning of distance learning courses of the Federal Police with an approach in Information Science - Pereira, Ricardo Henrique; Pinto , Adilson Luiz (Advanced Notes in Information Science, 2023)
This investigation deals with innovation applied to the context of corporate distance training in a public security institution of the Brazilian federal government. The importance of innovation transcends the private initiative and reaches the public entity, demanding evolution in internal processes and bringing better services to citizens. Restrictive budgetary situations and staffing reach are challenges faced. The approach of this study has an exploratory profile, seeking a review of the bibliography with a research method for investigating innovation to deliver information for planning educational management. A product life cycle approach is proposed as a process innovation in the planning of future educational actions. The expected result of this investigation is to bring efficiency to the educational planning process of distance training courses for the Federal Police. The continuity of the innovation process is a success factor for the modernization of governments.